Effectiveness Blended Learning in Reducing HIV-related Stigma and Discrimination among Nurses: A Queasy Experimental Design - Heni Purnama; Nyayu Nina Putri Calisanie; Linlin Lindayani; Taryudi Taryudi (Jurnal Keperawatan Padjadjaran, 2020)
Scale-up of stigma-reduction programs in healthcare settings has been slow in part due to lack of understanding and social norm associated with pre-existing stigma in HIV population. The application of blended learning can bridge the gap between theory and practice and make the learning experience more meaningful so that it can be applied as a way of learning to reduce stigma against PLWHA from healthcare professional. The aimed of this study was to determine the effectiveness of blended learning in reducing the stigma of nurses toward people with HIV/AIDS (PLWHA). This study used a quasi-experimental pre-post-test design with two groups (the intervention group and the control group). The samples in this study were nurses who worked at the public health center in Bandung. HIV-related stigma and discrimination (S&D) questionnaire was used to measure HIV-related stigma among nurses. Mean, standard deviation, frequency was used to explain demographic data and main variables. In the intervention (blended learning) group, there was a significant different of the mean score of HIV-related S&D before and after blended learning intervention with ∆ mean was 4.37 and (p = 0.001). In the control group, there was no significant different of those ∆ mean was 3.39 (p=0.459). A significant difference found in the post test mean score of HIV-related stigma and discrimination between intervention and control group [F=569.018, (p= 0.000)]. This study found that blended learning could reduce the HIV-related stigma and discrimination from nurses. This underscores the utility of this intervention to change the perceived of stigma and discrimination of health workers, as well as potential to generalize or adapt this intervention to other settings in the region and beyond.